Green Customer Behavior on Eco-Friendly Products: Innovation Approach - Alamsyah, Doni Purnama; Syarifuddin, Didin; Mohammed, Hayder Alhadey Ahmed (Department of Management, Faculty of Economics, Universitas Negeri Semarang, 2018)
This aim of the study investigates the correlation of perceived innovation, service innovation and green perceived value on eco-friendly products, to improve customer decision of product with moderation of sex and educational background. The study of eco-friendly product has been common in the world. Indonesia is a country which is not very good at circulation of eco-friendly product. The study is conducted with focuses on eco-friendly products; through experiment survey to customer who has bought eco-friendly products in Bandung city. The research found that perceived innovation, service innovation and green perceived value have correlation. However green perceived value as based of purchase decision of customer can only be improved by perceived innovation of eco-friendly products. Furthermore, sex and customer’s educational background can truly support the correlation of perceived innovation with green perceived value of customer. This research finding explained how important perceived innovation supported by the characteristics (sex, educational background) of customers.